2017
DOI: 10.1158/1078-0432.ccr-16-2152
|View full text |Cite
|
Sign up to set email alerts
|

KTN0158, a Humanized Anti-KIT Monoclonal Antibody, Demonstrates Biologic Activity against both Normal and Malignant Canine Mast Cells

Abstract: Purpose KTN0158 is a novel anti-KIT antibody that potently inhibits wild-type and mutant KIT. This study evaluated the safety, biologic activity and pharmacokinetic/pharmacodynamics profile of KTN0158 in dogs with spontaneous mast cell tumors (MCT) as a prelude to human clinical applications. Experimental Design Cell proliferation, KIT phosphorylation and mast cell degranulation were evaluated in vitro. KTN0158 was administered to 4 research dogs to assess clinical effects and cutaneous mast cell numbers. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…For the reason that the majority of GISTs express KIT which was retained in refractory GISTs after small molecule treatment, anti-KIT monoclonal antibodies were investigated in preclinical setting and might move forward to clinical trials in the future [27,28].…”
Section: The Diagnosis Of Gist From the Ihc Point Of View (>95%)mentioning
confidence: 99%
“…For the reason that the majority of GISTs express KIT which was retained in refractory GISTs after small molecule treatment, anti-KIT monoclonal antibodies were investigated in preclinical setting and might move forward to clinical trials in the future [27,28].…”
Section: The Diagnosis Of Gist From the Ihc Point Of View (>95%)mentioning
confidence: 99%
“…They provided proof of concept and confirmed that KIT could be accurately labeled in GISTs for detection of primary tumors, as well as for detection of small metastatic deposits that might be missed at the time of surgical resection. The recently developed humanized monoclonal antibody KTN0158 is being evaluated in dogs for therapeutic purposes and might eventually have potential for imaging …”
Section: Resultsmentioning
confidence: 99%
“…A single injection of anti-c-kit antibodies shortly after birth resulted in a prolonged suppression of melanoma, a greatly increased tumor-free period, and none of the animals injected with anti-c-kit antibodies died from cancer for 12 months after birth [ 99 ]. Another group of researchers developed humanized anti-c-kit monoclonal antibodies, KTN0158, that specifically interact with both mutant and wild-type c-kit and exhibit biological activity in normal and malignant mast cells [ 100 ]. In 2015, Kolltan Pharmaceuticals launched a phase I clinical trial of anti-c-kit monoclonal antibodies, KTN0158, as a monotherapeutic agent for the treatment of patients with gastrointestinal stromal tumors and other c-kit-positive tumors ( NCT02642016 ).…”
Section: Tumor Markers In Neuroblastomamentioning
confidence: 99%